Improving Basic Knowledge about Sports Injuries through Sports Injury Education for SMAN Keberkatan Olahraga Students - Nancy Sylvia Bawiling; Jein Jeilen Tampi; Muh Alif Kurniawan Sam; Rendi Alfani; Andi Herdinawaty Heril; Desy Yunita Utami; Muh Jamil Abdillah (Jurnal Pemberdayaan Masyarakat dan Komunitas, 2026)
Routine and intensive physical activity in a sports school environment carries a high risk of injury, which can lead to decreased physical performance or even cessation of sports activities if not handled properly. This study aims to improve students' knowledge about sports injuries through sports injury education interventions, identify the initial level of knowledge, and analyze the increase in students' understanding post-intervention. The research method used was a pre-experimental one-group pre-test and post-test design approach. The activity was carried out at the State Senior High School for Sports Talent (SMANKOR), involving 55 active students as respondents selected using a total sampling technique. Demographic characteristics showed that the majority of respondents were male (63.6%) and were in grade 10 (69.1%), with sports interests dominated equally by Karate (29.1%) and Badminton (29.1%). The results of the descriptive test showed an increase in the average score of students' knowledge from 6.96 in the pre-test to 8.4909 in the post-test. The Kolmogorov-Smirnov normality prerequisite test showed that the data were not normally distributed (p-value less than 0.05), so the hypothesis testing was diverted to the non-parametric Wilcoxon Signed Ranks Test. The results of this test produced a significance level of 0.000. Because the significance value is much smaller than 0.05 (0.000 less than 0.05). The conclusion of this study proves that providing sports injury education has a positive and significant effect on improving the basic understanding of SMANKOR students regarding sports injuries.